READING TO LEAD: THE BOOK CLUB AS AN ENTREPRENEURIAL DEVELOPMENT TOOL IN ACADEMIA (Revista Brasileira Multidisciplinar, 2024)
Entrepreneurship comprises personal and behavioral aspects that, permeated by the social and environmental context and the entrepreneur's path, enable the emergence of certain entrepreneurial behaviors and qualities. Despite the lack of focus on entrepreneurial activity in educational institutions in our country, especially in postgraduate programs, the importance of projects to disseminate entrepreneurship concepts for the creation of personal entrepreneurial characteristics in the academic environment is evident. In this way, the “Café ConsCiencia: Book Club” project is a remote initiative, with monthly meetings via the Biotechnology – Uniara channel, on YouTube, with the objective of exhibiting books related to the area of entrepreneurship, to disseminate the concepts among students, teachers, businesspeople, and anyone else interested, with the aim of promoting reflection, dialogue, cooperation and rapprochement between such actors in order to promote entrepreneurial actions in a network. The project took place between the months of August 2021 and June 2022 and a total of 8 books were discussed on the subjects of entrepreneurship and innovation, with guests in lives on the Uniara Biotechnology channel. In addition, it used social media to increase the reach of the project. The videos have reached a total of 508 views to date and were able to raise several discussions on the topics during the lectures. We also highlight that the project may continue with new editions, bringing new guests, books to be discussed and seeking greater reach on social media.
Keywords: book club; entrepreneurship; academy; leadership